Bridging the gap between basic and applied biology: towards preclinical translation - Ross L. Cagan; Monica J. Justice; George F. Tidmarsh (The Company of Biologists, 2013)
Summary To better translate basic research findings into the clinic, we are moving away from the traditional one-gene-one-phenotype model towards the discovery of complex mechanisms. In this Editorial, the new Editor-in-Chief and Senior Editors of Disease Models & Mechanisms (DMM) discuss the role that the journal will play in this transition. DMM will continue to provide a platform for studies that bridge basic and applied science, and, by demanding the rigorous assessment of animal models of disease, will help drive the establishment of robust standards of preclinical testing for drug development.